Customer Relationship Management (CRM) Strategy of PT ASDP Indonesia Ferry (Persero): A Customer Satisfaction and Digital Transformation Approach - Hasan Abdullah Muhammad; Fitri Adini Firdaus; Ni Ketut Mega Diana Putri (SITEKNIK: Sistem Informasi, Teknik dan Teknologi Terapan, 2025)
This study evaluates the CRM strategy of PT ASDP Indonesia Ferry through a mixed-methods approach combining survey data from 2,000 customers and in-depth interviews with company directors. The 2023 Customer Satisfaction Index score of 5.34 reveals improved but uneven performance, with walk-on passengers (5.39) significantly more satisfied than vehicle users (5.31). While digital initiatives like the Ferizy platform and service standardization programs show promise, key challenges emerge in three areas: persistent offline transaction preferences (80% among vehicle users), inconsistent service quality across branches (CSI range 5.13-5.41), and growing competitive pressures. The analysis identifies successful CRM pillars including digital transformation, service excellence programs, and targeted engagement strategies, but highlights the need for more segmented approaches to address distinct customer needs. Strategic recommendations emphasize enhanced digital integration with real-time tracking capabilities, operational improvements in fleet management, and continuous performance monitoring systems. These findings contribute practical insights for transportation service providers operating in archipelagic environments, demonstrating how CRM implementation must balance technological innovation with operational realities to achieve sustainable customer satisfaction improvements.